Et si les malentendus sociocognitifs faisaient ou défaisaient l'effet-maître ? - Sabine Kahn (Université de Provence, 2012)
This paper aims to take stock on the contributions and the limits of the "teacher-effects" researches, effects of processes - product type. It observes a real shift between the measurement tool (test) of the teaching efficiency and the expectation of programmatic texts, as it is the case for the French "socle commun", or the Belgian "Socles de competences", for example. The paper shows that a teacher - and his practices - "evaluated" efficient in a processes - product paradigm, loses this quality when the goal is to conduct the pupils to master the competences of the programs. A trend of researches emerges, devoted to the comprehension of this gap. It tempts, on the one hand, to evaluate real competences (and not single procedures) to locate the "product" of a teaching- learning device, and, on the other hand, to understand, by the mean of observations, what constitutes the difference in the teaching practices.